Starterkit Klinikalltag mit Schwerpunkt Psychiatrie - Elstner, Samuel; Schade, Christoph; Diefenbacher, Albert (MWV Medizinisch Wissenschaftliche Verlagsgesellschaft, 2015)
"Are you about to start your career as a young doctor or have you already gained some experience? You are surely clear: like in hardly any other discipline, you can start your day-to-day work with a huge foundation of theoretical knowledge. However, this will also require much more from you: efficient medical self-organization, the highest level of communicative skills in dealing with patients, colleagues and superiors, and last but not least leadership and management skills. However, you may not have these important requirements because your studies did not prepare you for them. Then you run the risk of not being able to concentrate your strength on the actual clinical tasks in the emotional and organizational thicket of the early days. The Everyday Clinic Starter Kit provides you with the right knowledge to start your career - apart from most study content and textbooks: How do I organize my day-to-day work as a doctor? What do I do in the event of an overload or crisis? How do I find my role in the station team and vis-à-vis superiors and colleagues? How do I use intuition, communication and cooperation and prepare for dealing with violence, suicide or addiction? Inevitably, these questions focus on the psychiatric challenges of the medical profession. The authors, of course also former entrants, prepare you for the exciting work with patients and everyone else involved in the organization of a hospital in such a way that your motivation is not harmed and you can enjoy the medical profession right from the start."